Effectiveness of procurement procedures on minimization of audit queries in public sector: A case of Tanzania Electric Supply Company Limited - Mayala, Mapesa Idaso (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Science in Procurement and Supply Chain Management (MSc-PSCM) of Mzumbe University, 2019